Design and Implementation of a Framework for Self-Configuring Devices Using TR-069 - Rachidi, Houda (Université d'Ottawa / University of Ottawa, 2011)
Communication network technologies have been evolving exponentially in the late decades. These innovations increase the network capabilities and open new horizons to creating novel and original services. The heterogeneity in equipment qualifications increases the level of complexity in the technological advancement. In such environment, service management has become an everyday challenge to service providers. Important efforts have been deployed to innovate in the exploitation of intelligent devices in the home and other private locations. In this Thesis, we propose a framework for self-configuration of devices within Hone Area Networks. We propose a device self-configuration architecture based on IBM Monitor-Analyze-Plan-Execute using Knowledge autonomic control loop. To prove the validity of our system architecture and support its applicability, we developed a prototype system that gives a general control loop implementation for device self-configuration using the CPE WAN Management Protocol. A video streaming scenario is implemented and used to evaluate validity our framework.
Keywords: Device Self-configuration; TR-069; CWMP; autonomic control loop; IBM MAPE-K